2016
DOI: 10.1093/treephys/tpw055
|View full text |Cite
|
Sign up to set email alerts
|

Single vessel air injection estimates of xylem resistance to cavitation are affected by vessel network characteristics and sample length

Abstract: Xylem resistance to cavitation is an important trait that is related to the ecology and survival of plant species. Vessel network characteristics, such as vessel length and connectivity, could affect the spread of emboli from gas-filled vessels to functional ones, triggering their cavitation. We hypothesized that the cavitation resistance of xylem vessels is randomly distributed throughout the vessel network. We predicted that single vessel air injection (SVAI) vulnerability curves (VCs) would thus be affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 59 publications
3
34
0
Order By: Relevance
“…This finding could imply that vessels in the same area of the leaf have similar vulnerability to cavitation or, more probably, that most vessels are not tested before gas is present in a neighbor with which they share pit connections. Combining the wide range of xylem vulnerability shown by single vessel air injection (Christman et al, 2012;Venturas et al, 2016) and our observation that vessels tend to cavitate mostly after their neighboring vessels are embolized suggests that the patchiness phenomenon is caused by highly resistant vessels that, once embolized, expose a whole region of less resistant conduits to gas. In accordance with the aforementioned vulnerability segmentation, it would make sense that these highly resistant vessels are located in hydraulically critical positions.…”
Section: Discussionmentioning
confidence: 57%
“…This finding could imply that vessels in the same area of the leaf have similar vulnerability to cavitation or, more probably, that most vessels are not tested before gas is present in a neighbor with which they share pit connections. Combining the wide range of xylem vulnerability shown by single vessel air injection (Christman et al, 2012;Venturas et al, 2016) and our observation that vessels tend to cavitate mostly after their neighboring vessels are embolized suggests that the patchiness phenomenon is caused by highly resistant vessels that, once embolized, expose a whole region of less resistant conduits to gas. In accordance with the aforementioned vulnerability segmentation, it would make sense that these highly resistant vessels are located in hydraulically critical positions.…”
Section: Discussionmentioning
confidence: 57%
“…Stem segments are cut from larger branches under water and connected to a hydraulic apparatus to measure their hydraulic conductance under low water pressure, before displacing embolism by a high‐pressure ‘flush’ and repeating measurements under low pressure to quantify maximum hydraulic conductance, and finally calculating PLC. Several alternative methods to generate VCs have been proposed and tested, including monitoring of acoustic emissions rate by dehydrating stems (Milburn, ; Tyree & Dixon, ; Jackson & Grace, ; Nolf et al ., ), real‐time measurements of hydraulic conductance of stems spinning in a centrifuge (Cochard, ; Li et al ., ), induction of embolism by positive air pressures applied to stems (Cochard et al ., ; Salleo et al ., ), single‐vessel air injection (Venturas et al ., ) and quantification of the air volume extracted from progressively dehydrated branches (Pereira et al ., ). All these methods can be potentially affected by pitfalls and artefacts (Cochard et al ., ), and the recent literature is rich in controversies regarding their validity (Jansen et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Different methods used to generate vulnerability to cavitation curves may produce different results. The standard centrifuge technique as used in the present study, when compared with other techniques, has generally been found to produce reliable results (e.g., Sperry, Christman, Torres‐Ruiz, Taneda, & Smith, ; Jacobsen & Pratt, : Hacke et al, : Venturas et al, ); however, some have reported potential measurement errors with similar static rotor designs (Choat et al, ; Torres‐Ruiz et al, ). This has led to the recommendation that more than one method be used in order to evaluate methods within studies (Hacke et al, ; Sperry et al, ).…”
Section: Methodsmentioning
confidence: 69%
“…We selected a subset of species of special interest to examine using single‐vessel air injection (SVAI) as described in Venturas et al (). The first species that we selected was Laurus nobilis , which is a basal angiosperm that contains very short vessels (Jacobsen et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation